2004
DOI: 10.1111/j.1365-313x.2004.02226.x
|View full text |Cite
|
Sign up to set email alerts
|

The MADS‐box gene DAL1 is a potential mediator of the juvenile‐to‐adult transition in Norway spruce (Picea abies)

Abstract: SummaryProgression through the plant life cycle involves change in many essential features, most notably in the capacity to reproduce. The transition from a juvenile vegetative and non-reproductive to an adult reproductive phase is gradual and can take many years; in the conifer Norway spruce, Picea abies, typically 20-25 years. We present a detailed analysis of the activities of three regulatory genes with potential roles in this transition in Norway spruce: DAL1, a MADS-box gene related to the AGL6 group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 63 publications
5
97
1
5
Order By: Relevance
“…In studies of the molecular mechanisms of tree aging, many age-related genes have been identified (Busov et al 2004;Carlsbecker et al 2004;Diego et al 2004;Fernández-Ocaña et al 2010;García-López et al 2014;Hutchison et al 1990;Li et al 2010Xu et al 2016;Zhang et al 2016), such as miR156 (Wang et al 2011b) and Flowering Locus T (Böhlenius et al 2006;Hsu et al 2006Hsu et al , 2011, and some have been used to change the agronomic traits of plants (Flachowsky et al 2012;Kotoda et al 2006;Li et al 2013a;Yamagishi et al 2014). Larix kaempferi is a forest tree of important ecological and economic value, widely grown in the Northern Hemisphere, but its genome has not been sequenced.…”
Section: Communicated By F Gugerlimentioning
confidence: 99%
“…In studies of the molecular mechanisms of tree aging, many age-related genes have been identified (Busov et al 2004;Carlsbecker et al 2004;Diego et al 2004;Fernández-Ocaña et al 2010;García-López et al 2014;Hutchison et al 1990;Li et al 2010Xu et al 2016;Zhang et al 2016), such as miR156 (Wang et al 2011b) and Flowering Locus T (Böhlenius et al 2006;Hsu et al 2006Hsu et al , 2011, and some have been used to change the agronomic traits of plants (Flachowsky et al 2012;Kotoda et al 2006;Li et al 2013a;Yamagishi et al 2014). Larix kaempferi is a forest tree of important ecological and economic value, widely grown in the Northern Hemisphere, but its genome has not been sequenced.…”
Section: Communicated By F Gugerlimentioning
confidence: 99%
“…Juvenility genes are mostly located upstream of these genes that directly control flowering. Carlsbecker et al (2004) reported that DAL1 is related to juvenility in the conifer Norway spruce. DAL1 is considered to be the conifer homolog of Arabidopsis AGAMOUS-LIKE6 (AGL6).…”
Section: Introductionmentioning
confidence: 99%
“…La función de los genes del clado AGL6 en Arabidopsis thaliana (AGL6 y AGL13) no se ha demostrado, pero tanto estos como otros genes relacionados en otras especies se expresan en órganos florales y óvulos Immink et al, 2003) y pueden influir en la floración al ser expresados ectópicamente (Carlsbecker et al, 2004).…”
Section: Clasificación Y Filogenia De Los Genes Mads-boxunclassified
“…MtAGL6, al igual que su ortólogo PsMADS5 (Ferrándiz, 1996), tiene expresión específica en flor, un patrón de expresión común para los genes tipo AGL6 (Ma et al, 1991;Mouradov et al, 1998;Boss et al, 2002;Mena et al, 1995;Petersen et al, 2004;Hsu et al, 2003;Moon et al, 1999;Carlsbecker et al, 2004;Fan et al, 2007). Este patrón de expresión específico, sugiere que juega un papel primario en el desarrollo de los órganos florales.…”
Section: Agl6unclassified
See 1 more Smart Citation